Interaction of 3H-defibrotide with cultured human umbilical vein endothelial cells - YALÇIN, AHMET SUHA (My University, 1990)
Defibrotide is a profibrinolytic and antithrombotic drug which seems to modulate endothelial cell function. In this study, a method for radioactive labeling of the drug and its interaction with cultured endothelial cells is proposed. 3H-Acetic anhydride was used to label defibrotide. Endothelial cells obtained by collagenase treatment of human umbilical cord veins were cultured in 24-welled plastic culture dishes. Binding experiments were carried out by incubating cell cultures with media containing various concentrations of labeled defibrotide. Our results showed that labeled defibrotide has a KL value of 4.2 micrograms/ml for endothelial cells. Although the presence of a specific transporter is possible, the high molecular weight of the fraction used suggests that the interaction is binding to a specific receptor.
Keywords: Humans; Kinetics; Cells, Cultured; Endothelium, Vascular; Fibrinolytic Agents; Polydeoxyribonucleotides; Binding Sites